KALENDER UMM AL-QURA (Studi Pergeseran Paradigma Sistem Kalender di Kerajaan Arab Saudi) - Musonnif, Ahmad (Ahkam: Jurnal Hukum Islam, 2015)
Umm Al Qura calendar is a new calendar issued by the SaudianKingdom for civil purpose which is based on hisab (based oncomputation) system. The reason for issuing such kind of calendar isto unite Moslems all over the world especially in deciding the first dayof Ramadhan, Idul Fitri, and Idul Adha. The hisab system of Umm alQura calendar often leads to a controversy because it comes up withdifferent result in determining the first day of a month compared tothe other calendars which use rukyat (based on observation) system.However, this kind of calendar is widely adopted in the areas whereMoslems are minority.Kata kunci: Kalender Umm al-Qura, Pergeseran Paradigma, SistemKalender Kerajaan Arab Saudi